Effect of different surfactants on the shape, growth and photoluminescence behavior of MnWO4 crystals synthesized by the microwave-hydrothermal method - Almeida, M. A. P.; Cavalcante, L. S. [UNESP]; Varela, José Arana [UNESP]; Siu Li, M.; Longo, Elson [UNESP] (Elsevier B.V., 2012)
In this communication, we report the effect of different surfactants [cetyltrimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS) and sodium bis(2-ethylhexyl)sulfosuccinate (AOT)] on the shape, growth and photoluminescence (PL) behavior of manganese tungstate (MnWO4) crystals synthesized by the microwave-hydrothermal (MH) method at 413 K for 45 min. These crystals were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), ultraviolet-visible (UV-vis) absorption spectroscopy and PL measurements. XRD patterns proved that these crystals have a monoclinic structure. FE-SEM images showed that MnWO4 crystals exhibit different shapes and growth mechanisms depending on the surfactant employed. The CTAB cationic surfactant promotes the hindrance of small nuclei that leads to the formation of flake-like nanocrystals, while SDS and AOT anionic surfactants promote a growth of crystals to plate-like and leaf-like crystals due to considerable size effect of counter-ions (RSO4- and RSO2O-) and an increase in Na+ ion remnants. UV-vis absorption spectroscopy revealed different optical band gap values due to modifications in the shape, surface and crystal size. Finally, the effect of surfactants on the crystal shapes and average crystal size distribution causing changes in the PL behavior of MnWO4 crystals was explained. (C) 2011 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: MnWO4; Microwave-hydrothermal; Surfactants; Photoluminescence